Contrasting glacier behaviour in southernmost South America and northernmost Antarctica in response to climate change - (:unkn) unknown (My University, 2025)
Chile, as an emerging economy, faces the challenge of sustainable development using its natural resources and associated ecological services, affected by a global-scale anthropogenic climate change. In this scenario, detailed knowledge of the natural environment is needed because of the strengthening of current and future environmental regulations including Chile’s environmental impact assessment system (EIA). This is especially true for glacier research, at a time when a new glacier law is being discussed in Congress. The main challenge is how to combine economic growth with minimal environmental impacts based on evidence of change assessed from sensitive natural indicators. Glaciers react very sensitively to global warming since they adjust their geometry mainly in response to variations in temperature and precipitation (Vaughan et al., 2013). As such, they have become unique icons of climate change. A vast majority of glaciers are retreating and losing mass at a planetary scale at an accelerated rate in response to global warming (IPCC, 2019). Most mountain glaciers could disappear by the end of this century based on current glacier behaviour and considering future scenarios of climate change, although large ice masses would persist well beyond 2100 (Zemp et al., 2019). Within this context of glacier recession, there are only a few regions in the world where some glaciers have shown advance and/or mass gain (IPCC, 2019), mainly due to local climate forcings or glacier dynamics. The Cordillera Darwin in southernmost South America is one of the few regions on Earth where some glaciers are advancing while most others are retreating. The causes for such behaviour are not yet understood. This project aims at studying glaciers in 2 target areas, the western Cordillera Darwin (4 glaciers) and King George Island (2 glaciers), exhibiting different behaviour, including glacier retreat, relatively stationary fronts and glacier advance. The climate conditions and mass balance will be characterised, applying an energy and mass balance model to help elucidate the causes of the glacier behaviour. Ice flow and glacier geometry will be studied as well, to investigate possible changes in ice dynamics. The main objective is to elucidate the causes that drive contrasting glacier behaviour in southernmost South America and northernmost Antarctica, which are affected by similar climate forcing dominated by the low-pressure subpolar belt associated with year-round westerly winds. Methods will include the deployment of new weather stations to determine climate conditions; geodetic mass balance utilizing satellite data, DEMs generated from UAV imagery employing structure from motion, terrestrial LiDAR and field GNSS measurements; glaciological mass balance using stakes and shallow firn cores; calving front processes through bathymetry, terrestrial LiDAR, time-lapse cameras, CTD to characterise the water column properties, ADCP for ocean currents and water pressure sensors to detect wave activity linked to calving; glacier area changes using satellite data and vegetation colonization chronologies; energy flux and climatic mass balance modelling through a coupled atmosphere and snowpack/ice model. The project will reinforce the scientific and technological capacities of three regional research groups based at Punta Arenas: the Chilean Antarctic Institute (INACH), Universidad de Magallanes (UMAG) and Centre for Quaternary Studies (CEQUA), including strong international cooperation with Humboldt-Universität zu Berlin, Germany and the Federal University of Rio Grande, Brazil. Two doctoral students and one Master student from the University of Magallanes will perform a graduate thesis as part of the project.